STRATEGI PENGELOLAAN DAYA TARIK WISATA AIR TERJUN LEKE-LEKE DI KABUPATEN TABANAN BALI - Ni Nyoman Ardani; L.K.Herindyah Kartika Yuni; Tri Wahyuni Surya Atmaja (Journal of Tourism and Interdiciplinary Studies, 2023)
Tourist attractions management plays very important role to support the sustainability of a destination. This research aim is to describe the appropriate strategy for management by knowing the internal (strengths & weaknesses) and external (opportunities & threats) factors of the tourist attraction of Leke-Leke Waterfall. This research uses qualitative analysis methods and SWOT analysis to determine strategies that are right on target. Data collection techniques in this research include observation, documentation and interviews with the management of Leke-Leke Waterfall, community leaders and tourists. The research results show that Leke-Leke Waterfall has four management strategies that might be implemented, namely (1) management of natural resources and a sustainable environment, (2) Management of economic sustainability which has an impact on the surrounding community by continuing to provide education to the community, (3) Management of increasing cultural integration by actively developing art that can be presented to tourists. (4) Management of the value of education and learning for the community by increasing human resources in tourism management including the preparation of competent and certified tour guides.